Intestinal occlusion secondary to Bochdalek diaphragmatic hernia. - Cantileno, Pablo; López Penza, Patricia (Cirugía del Uruguay, 2021)
Bochdalek hernia, caused by a defect in the left posterolateral closure of the diaphragm, is diag-nosed in children. Diagnosis in adulthood is rare, it can manifest as an imaging finding, present with nonspecific symptoms and an acute abdomen due to intestinal obstruction that requires emergency surgical treatment. A clinical case of a patient with a picture of intestinal obstruction is presented, the image-genological analyzes confirm the diagnosis of a Bochdalek diaphragmatic hernia